Skip to content
Tags

,

More on ‘and’ and ‘&&’

June 22, 2011

Seems that

c = a and b

is equivalent to

(c = a) && b

and

c = a && b

is equivalent to

c = (a and b)
Advertisements

From → Uncategorized

Leave a Comment

Leave a Reply

Fill in your details below or click an icon to log in:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out / Change )

Twitter picture

You are commenting using your Twitter account. Log Out / Change )

Facebook photo

You are commenting using your Facebook account. Log Out / Change )

Google+ photo

You are commenting using your Google+ account. Log Out / Change )

Connecting to %s

%d bloggers like this: